The Effect of Training and Work Discipline on Employee Performance with Career as A Moderating Variable for Employees at PT PLN (Persero) Implementation Unit Customer Service North Medan - Riston Sihaloho; Kiki Farida Ferine; Sri Rahayu (International Journal of Economics, Management and Accounting (IJEMA), 2025)
This study aims to analyze the influence of training, work discipline, and career development on employee performance, as well as to examine the moderating role of the interaction between variables on performance. The research approach used was quantitative with Partial Least Square (PLS) analysis technique. Data was obtained through distributing questionnaires to 65 respondents. The results showed that training, work discipline, and career development have a positive and significant influence on employee performance. This indicates that the better the training is provided, the higher the discipline, and the clearer the direction of career development, the more employee performance will improve. Meanwhile, the first and second moderating effects did not have a significant influence, so the interaction between variables did not strengthen the relationship on performance. This finding implies that organizations need to focus more on strengthening the main variables in an effort to improve employee performance.